IMPROVING THE EFFICIENCY OF BUSINESS COMMUNICATIONS BASED ON THE USE OF DIGITAL CHANNELS - A. Krylov; G. Kuzina; I. Golyshkova; R. Yazintsev (Вестник университета)
The efficiency of use of digital channels has been analyzed, based on the results of a study, carried out on the example of trade centers in Russia. The basic trends of the advertising market and prospects of its development have been examined. Advantages and disadvantages of the most promising types of communication, namely the content and mobile advertising, have been identified. The approach based on the use of cross-platform planning has been offered. The recommendations at the choice of the digital tools for companies of small, medium and large businesses have been given, the efficiency indicators have been adduced.